(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In this paper,the notion of gb-open sets in topological spaces is ap- plied to study a new class of functions called contra gb- continuous functions as a new generalization of contra continuity and obtain their characterizations and properties.